2020
DOI: 10.5734/jgm.2020.17.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of chromosomal microarray for pathogenic genomic imbalance in fetuses with increased nuchal translucency but normal karyotype

Abstract: Purpose: To evaluate the additive value of prenatal chromosomal microarray analysis (CMA) in assessing increased nuchal translucency (NT) (≥3.5 mm) with normal karyotype and the possibility of detecting clinically significant genomic imbalance, based on specific indications. Materials and Methods: Invasive samples from 494 pregnancies with NT ≥3.5 mm, obtained from the Research Center of Fertility & Genetics of Hamchoon Women's Clinic between January 2019 and February 2020, were included in this study and CMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Though the American College of Obstetricians and Gynecologists (ACOG) recommended that the usefulness of CMA in detecting chromosomal abnormalities remains ambiguous and conventional karyotype analysis remains the preferred method of prenatal diagnostic testing [ 23 ]. In the past years, more and more studies have demonstrated advantages of CMA over karyotype analysis in prenatal diagnosis [ 10 , 13 ]. In addition, a cut-off value of NT with 3.0 or 3.5 nm was used as the threshold in most investigations on the association between CMA and NT, the objective of this study was to determine whether CMA should be recommended on fetuses with NT ≥ 2.5 mm, but normal karyotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the American College of Obstetricians and Gynecologists (ACOG) recommended that the usefulness of CMA in detecting chromosomal abnormalities remains ambiguous and conventional karyotype analysis remains the preferred method of prenatal diagnostic testing [ 23 ]. In the past years, more and more studies have demonstrated advantages of CMA over karyotype analysis in prenatal diagnosis [ 10 , 13 ]. In addition, a cut-off value of NT with 3.0 or 3.5 nm was used as the threshold in most investigations on the association between CMA and NT, the objective of this study was to determine whether CMA should be recommended on fetuses with NT ≥ 2.5 mm, but normal karyotypes.…”
Section: Discussionmentioning
confidence: 99%
“…CMA is a high-resolution and high-throughput molecular detection technology for detecting human genomic DNA copy number variation, which shows advantages over karyotyping both in postnatal diagnosis and prenatal diagnosis. According to the most recent research, applying of CMA in fetuses with elevated NT identified additional pathogenic copy number variants (CNVs) over that from karyotyping in 3.7% [ 10 ]. However, no global consensus on the cut-off value of NT for CMA has been reached currently.…”
Section: Introductionmentioning
confidence: 99%